Knowledge Management for Social Workers Involved in Disaster Planning and Response in Malaysia: An Action Research Approach - Raman, Murali; Dorasamy, Magiswary; Muthaiyah, Saravanan; Kaliannan, Maniam; Muthuveloo, Rajendran (Springer, 2011)
This paper explores the idea of using a knowledge management system to support disaster planning and response (DPR) efforts for social workers involved in such efforts in Malaysia. The study was funded by the Government of Malaysia. Canonical Action Research was used to conduct the study. The Malaysian Association of Social Workers (MASW) was the client organization. The study began with problem formulation to ascertain issues inherent in DPR within the MASW. The next phase of the research, involved action planning-the team considered implementing a web-based knowledge management (KM) system to support DPR efforts for the organization. Post intervention, we conducted an evaluation of our action, based on interviews with key members affiliated to the MASW. Our findings are in tandem with prior work that has examined the role and relevance of KM systems in light of DPR efforts. The client organization in general forms the view that KM systems can support DPR efforts by providing vital information (pertaining to DPR) and assist the overall coordination and planning efforts for the organization.